SISTEM INFORMASI PENGAWASAN KENDARAAN ANGKUTAN BARANG PADA JEMBATAN TIMBANG UNTUK PENENTUAN PELANGGARAN MUATAN LEBIH DAN DAMAGE FACTOR (Studi Kasus Daerah Istimewa Yogyakarta) - Simatupang, Rudy Handry Halomoan; Sartono, Wardhani; Christady H, Hary (Civil Engineering Forum Teknik Sipil, 2008)
Government has determined maximum limit of axle pressure for vehicle passing in the road of MST (Heaviest Axle Load) < 8 ton, MST 8 ton and MST 10 ton. But, the problem is that there are many overloaded freight vehicles. The lack of control and law application causes the happening of case like overloaded resulting in faster damage than the planned duration and traffic accident involving freight truck. Daerah Istimewa Yogyakarta is a province connecting East java – Central Java – West Java. It has potential to serve traffic flow, either passenger or freight. Therefore it needs a system to control freight vehicle in measuring bridge. Information System of Freight vehicle control (SIWASAL) used reaction analysis of freight vehicle dimension and the calculation of damage factor. Axle configuration discussed based on field observation and load survey carried out by PUSTRANS JALAN in 2002 in Pantura, comprised of 1.1, 1.2, 1.22, 11.22, 1.2+22 (coupled freight vehicle), 1.22+22 (coupled freight vehicle), 1.2-2 (attached freight vehicle), 1.2-22 (attached freight vehicle), 1.22-22 (attached freight vehicle), 1.22-222 (attached freight vehicle). The result of this system helped the operator of measuring vehicle weight limit’s in applying the law and could be used by the government as the database in controlling, planning, maintaining and developing road pavement and give information, either to the employer of freight vehicle and society. The release of data process will present the number of the vehicle, trade mark/type, the name of the company, origin/destination, type of goods loaded, JBB, JBI, the weight of each vehicle axle, loading capacity, MST and vehicle damage factor. The recapitulation of freight vehicle control comprised of vehicle type, the name of the company, origin, destination, type of goods and axle configuration comprising of damage factor amount presented in the form of graphic periodically.